Optimization of Extraction Lannea coromandelica for Antioxidant Activity using Analytical Factorial Design Approach : Optimisasi Ekstraksi Tanaman Lannea coromandelica Sebagai Antioksidan dengan Pendekatan Analisis design Faktorial - AR, Muh. Azwar; Hikma, Nurul; Yasir, Budiman; Asril Burhan, Asril; Khairuddin, Khairuddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: The yield of active compound in a plant can be affected by the extraction method, such as variety of solvent and extraction technique used. Objectives: This study aimed to optimize the yield of Lannea coromandelica leaf extract using several types of solvent and extraction techniques and evaluate the antioxidant activity of the extracts. Material and Methods: This study used a variety of solvent like distilled water, ethanol, n-hexane, and ethyl acetate with maceration, reflux, and sonication extraction techniques. The extract obtained was calculated for the percent yield and analyzed for their antioxidant activity using the DPPH method by UV -Vis Spectrophotometry with 523.5 nm maximum wavelength. The antioxidant activity was analyzed by factorial design analysis in Minitab 21 software. Results: The highest percentage yields was obtained from the extract with ethanol solvent, followed by distilled water, ethyl acetate and n-hexane. The highest extraction techniques was obtained from reflux and followed by maceration and sonication extracts. Analytical factorial design analysis showed that the linearity of solvent variation and extraction technique had a significant effect (P>0.05). From the analysis, it was found that there was a significant difference between the effect of the solvent on the antioxidant activities compared to the extraction technique. The extracts obtained have a very strong antioxidant activity against DPPH radicals. T Conclusions: L. coromandelica plant aquadest extract has potential to be developed in optimalization extraction method.